Nursing assistant/nurse aide exam. (Learning Express, 2016)
"This newly expanded and completely revised guide provides all the comprehensive information needed to master the official certification exams for Certified Nursing Assistants. Based on national standards for CNAa and geared toward the NNAAP exam, inside is the most comprehensive practice available for prospective nurse aides and nursing assistants,"--Amazon.com.